Chest Ultrasound- A New Way To Diagnose (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Chest ultrasound is a new modality and a new way of scanning and investigating the chest and lungs. It is getting popular both with the clinicians and the sonologists as it is cheap, easily available and portable and so can be taken to the patient’s bedside in the Intensive Care Unit (ICU) or High Dependency Unit (HDU). Its need is increasing with the passage of time. It is more used nowadays with the prevalence of Dengue fever to detect pleural effusion and also the degree of pleural effusion. Its use also increased in the ICU and HDU during COVID pandemic to detect pneumonia. Even for carrying out procedures like pleural fluid aspiration for diagnostic or therapeutic purpose its usage is increasing for accurate and quick access to the targeted area of fluid collection. It is also being used to exclude any collection at the site of aspiration so as to treat it before discharge of the patient.J Bangladesh Coll Phys Surg 2024; 42: 189-193